ETIKA KONSELING DALAM ERA DIGITAL: ANCAMAN DAN PELUANG INTERNASIONAL - Happy Karlina Marjo; Ani Musyarofah; Lia Amalia Putri (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Counseling becomes a necessity, because the essence of counseling is the help of an expert counselor given to someone to solve their problems. In providing these services, a counselor is governed by ethics, attitudes and personal qualities for the counselor to behave. Professional ethical values are very important in the helping profession. The code of ethics for counselors is established by the counselor professional institution. For the Indonesian territory, the code of ethics for counselors is determined by the Indonesian Counseling Guidance Association, which is abbreviated as ABKIN. A code of ethics is a guide or guideline for professional behavior or a moral foundation that is practiced, secured and upheld by counselors as members of professional organizations. The aim of this research is to describe the professional ethics of counselors in counseling guidance services in the digital era. The method used in this research is a literature study with a qualitative descriptive approach. The data source comes from collecting documents in the form of books and previous research originating from various references. The data analysis technique used is descriptive analysis. The results of this research show that online counseling ethics takes the form of virtual counseling technology, websites, email, video conferences, instant messaging, computers and other social networks. Therefore, online counselors need to be professional in conducting virtual counseling by paying attention to ethics.